Alat Bantu Jalan Tuna Netra Menggunakan Sensor Ultrasonik Berbasis Mikrokontroller - Rusito; Dani Setiyawan (STEKOM PRESS, 2020)
For blind people, assistive devices to carry out daily activities are needed. If you don't use assistive devices, blind people will experience difficulties when carrying out daily activities such as reaching the obstacles that are near them. In designing the system using the Arduino UNO R3 microcontroller board as a controller, five ultrasonic proximity sensors to determine the distance and position from the user to the front and lower obstacles. In addition, the MP3 module and headseat are used as a marker for sound in the form of sound when detecting an object and the SIM800L module is used to send SMS and the GPS module is used to determine coordinates. The validation test shows the value of 31.5 is between 31- 40 which means that it is located in a Very Good (Valid) value. Keywords: Walking Aid, Blind, Ultrasonic Sensor, Microcontroller, Arduino Uno, GPS